Imaging Considerations in Spinal Cord Evaluation - Shea, Alice C.; Kuo, Anderson H.; Hsu, Liangge (Seminars in Neurology, 2021)
Multiple diverse pathologies result in the clinical presentation of myelopathy. The preferred way to image the spinal cord depends on clinical history, anatomic site of interest, and patient issues limiting certain imaging modalities. This radiology-focused article discusses pertinent physiological considerations, reviews basic and newer imaging techniques, and examines several distinct disease entities in order to highlight the key role of imaging in the work-up of myelopathy.
Keywords: myelopathy; spinal cord; imaging; radiology